The role of the PGE2EP system in the regulation of sodiumpotassium-ATPase protein levels and cell survival in the M-1 cortical collecting duct cell line - Paris, Genevieve (University of Ottawa (Canada), 2011)
Prostaglandin (PG) E2 is highly produced in the kidney and regulates sodium reabsorption, which is driven by the Na +/K+-ATPase (NKA) pump. It has been reported that high salt affects the activity of NKA in the cortical collecting duct. The current study addresses the role of PGE2 in NKA modulation and we hypothesize that PGE2 is acting via the EP4 receptor to increase NKA protein levels in hypertonic conditions. We demonstrated by immunoblotting an increase in NKA steady state levels of protein and activity in hypertonic conditions. Hypertonicity also stimulates cyclooxygenase (COX)-2 and PGE 2 production and modulates EP receptor mRNA expression. Involvement of PGE2 in NKA regulation was determined by COX inhibition (indomethacin and ibuprofen) and EP receptor antagonism (L-161 982 (EP4), SC51089 (EP1)). With the exception of L-161 982, no change in NKA protein levels was observed, suggesting that NKA regulation is independent of PGE 2 in high salt. Our results also indicated that PGE2 is not involved in cell survival and that L161 982 increases apoptosis, which can explain the decrease in NKA levels in high salt.
Keywords: Biology, Molecular.